Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

A planet of mass M has a moon of mass m in a circular orbit of radius R. An object is placed between the planet and the moon on the line joining the center of the planet to the center of the moon so that the net gravitational force on the object is zero. How far is the object placed from the center of the planet

Sagot :

Answer:

r =[tex]\frac{ 1 \pm \sqrt{ \frac{m}{M} } }{1 - \frac{m}{M} }[/tex]

Explanation:

Let's apply the universal gravitation law to the body (c), we use the indications 1 for the planet and 2 for the moon

          ∑ F = 0

           -F_{1c} + F_{2c} = 0

             F_{1c} = F_{2c}

let's write the force equations

             [tex]G \frac{m_c M}{r^2} = G \frac{m_c m}{(d-r)^2}[/tex]

where d is the distance between the planet and the moon.

              [tex]\frac{M}{r^2} = \frac{m}{(d-r)^2}[/tex]

             (d-r)² = [tex]\frac{m}{M} \ \ r^2[/tex]  

              d² - 2rd + r² = \frac{m}{M} \ \ r^2

              d² - 2rd + r² (1 - [tex]\frac{m}{M}[/tex]) = 0

              (1 - [tex]\frac{m}{M}[/tex])  r² - 2d r + d² = 0

we solve the second degree equation

              r = [2d ± [tex]\sqrt{ 4d^2 - 4 ( 1 - \frac{m}{M} ) }[/tex] ] / 2 (1- [tex]\frac{m}{M}[/tex])

              r = [2d ±  2d [tex]\sqrt{ \frac{m}{M} }[/tex]] / 2d (1- [tex]\frac{m}{M}[/tex])

              r =[tex]\frac{ 1 \pm \sqrt{ \frac{m}{M} } }{1 - \frac{m}{M} }[/tex]

there are two points for which the gravitational force is zero

The distance between object from planet will be "[tex]\frac{R}{[1+\sqrt{\frac{m}{M} } ]}[/tex]".

According to the question,

Let,

  • Object is "x" m from planet center = R - x
  • Gravitational force = 0
  • Mass of object = m₁

As we know,

→ [tex]Prerequisites-Gravitational \ force = \frac{GMm}{r^2}[/tex]

Now,

→ [tex]\frac{GMm_1}{x^2} = \frac{Gmm_1}{(R-x)^2}[/tex]

→ [tex]\frac{(R-x)^2}{x^2} = \frac{m}{M}[/tex]

→     [tex]\frac{R-x}{x} =\sqrt{\frac{m}{M} }[/tex]

→          [tex]x = \frac{R}{[1+ \sqrt{\frac{m}{M} } ]}[/tex]

Thus the answer above is appropriate.          

Learn more:

https://brainly.com/question/11968775